The analysis on the policy of access to economically affordable housing in China: an area calculation model based on the incentive mechanism design - Zhang, Jiankun; Yuan, Jingfeng; J. Skibniewski, Mirosław (International Journal of Strategic Property Management, 2011)
Currently, the subject of housing in China is of great interest to many researchers, since improvements in living conditions for the largest population in the world have not kept pace with the territory's economic growth. This paper describes basic social housing situations in China, and assesses the inequality in housing reform since 1990s as a result of overall economic improvement. In order to reduce the degree of inequality in China's social housing, this paper is focusing on the policy management of access to economically affordable housing because housing affordability in China is a pressing social and economic issue, particularly for low-income families due to an unreasonable mechanism. The related policies are analyzed in is paper by using incentive mechanism design, which reveals that supervision and announcement system, the restriction in current mechanism, and the area of economically affordable house are critical for the effectiveness of present polices. Furthermore, a housing area calculation model based on the incentive mechanism design is presented and an illustrated case of Beijing City is also conducted, which can maximize the utility of government considering incentive compatibility. Finally, some policy suggestions are explored including enhancing external environment and establishing internal mechanism.First Publish Online: 5 Oct 2011